2018
DOI: 10.1002/jcb.27286
|View full text |Cite
|
Sign up to set email alerts
|

miR‐383 promotes cholangiocarcinoma cell proliferation, migration, and invasion through targeting IRF1

Abstract: Interferon regulatory factor 1 (IRF1) has been found to serve as a tumor suppressor in cholangiocarcinoma, and enabled prediction of clinical progression and prognosis in our previous study. The objective of the current study is to screen and identify valuable microRNAs (miR), which target IRF1 to regulate cholangiocarcinoma cell proliferation, migration, and invasion. High expression of miR-383 was observed in cholangiocarcinoma tissues and cells. Meanwhile, we found the predicted binding site of miR-383 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
(152 reference statements)
0
34
0
Order By: Relevance
“…26 Functionally, miR-383 serves as a tumor-suppressive miRNA in the abovementioned human cancer types. On the contrary, miR-383 is upregulated in cholangiocarcinoma 27 and stimulates cancer progression. To our knowledge, this study is the first to show that miR-383 expression is low in ESCC and that miR-383 directly targets SP1 mRNA in ESCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Functionally, miR-383 serves as a tumor-suppressive miRNA in the abovementioned human cancer types. On the contrary, miR-383 is upregulated in cholangiocarcinoma 27 and stimulates cancer progression. To our knowledge, this study is the first to show that miR-383 expression is low in ESCC and that miR-383 directly targets SP1 mRNA in ESCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The latter was chosen for experimental verification because this miRNA has frequently been implicated in multiple types of human tumors. [23][24][25][26][27] The luciferase reporter assay was performed to test whether miR-383 can directly bind to FGD5-AS1 in ESCC cells. Either reporter plasmid FGD5-AS1-wt or FGD5-AS1-mut was transfected into TE-1 and Eca109 cells along with either agomir-383 or agomir-NC.…”
Section: Fgd5-as1 Interacts With Mir-383 and Sponges Mir-383 In Escc mentioning
confidence: 99%
“…In ccA, certain miRNAs have been previously demonstrated to exert stimulatory/suppressive effects on cancer progression (7). For example, miR-383 was found to act as a tumor suppressor in ccA and inhibits tumor development through decreasing the expression of interferon regulatory factor 1 (8). Through inhibiting aldolase A translation, miR-122-5p decreased bile duct carcinoma cell proliferation and promoted cell apoptosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…Using bioinformatics analysis and luciferase assay, we found that miR-216a-5p and miR-383-5p could directly regulate TIPRL expression through targeting the 3′-UTR of TIPRL. In recent years, accumulating evidence has demonstrated that miR-216a-5p and miR-383-5p are significantly elevated and function as oncogenic miRNAs in a variety of tumors ( 25 31 ). In particular, previous study have shown that miR-216a promotes invasion and metastasis in hepatocellular carcinoma through targeting TSLC1, PTEN, and SMAD7 ( 25 27 ), which is further confirmed in a variety of cell models ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, previous study have shown that miR-216a promotes invasion and metastasis in hepatocellular carcinoma through targeting TSLC1, PTEN, and SMAD7 ( 25 27 ), which is further confirmed in a variety of cell models ( 28 30 ). Moreover, it has been reported that miR-383 promotes cholangiocarcinoma cell invasion and proliferation by suppressing IRF1 ( 31 ). More importantly, in gastric cancer, miR-216a is significantly upregulated ( 32 ), and elevation of miR-216a would favor a worse clinical outcome ( 33 ).…”
Section: Discussionmentioning
confidence: 99%